Identification and Immunogenicity of Group A Streptococcus Culture Supernatant Proteins - Lei, Benfang (American Society for Microbiology, 2000)
Extracellular proteins made by group A Streptococcus (GAS) play critical roles in the pathogenesis of human infections caused by this bacterium. Although many extracellular GAS proteins have been identified and characterized, there has been no systematic analysis of culture supernatant proteins. Proteins present in the culture supernatant of strains of serotype M1 (MGAS 5005) and M3 (MGAS 315) mutants lacking production of the major extracellular cysteine protease were separated by two-dimensional gel electrophoresis and identified by amino-terminal amino acid sequencing and interrogation of available databases, including a serotype M1 genome sequence. In the aggregate, amino-terminal amino acid sequence data for 66 protein spots were generated, 53 unique sequences were obtained, and 44 distinct proteins were identified. Sixteen of the 44 proteins had apparent secretion signal sequences and 27 proteins did not. Eight of the 16 proteins with apparent secretion signal sequences have not been previously described for GAS. Antibodies against most of the apparently secreted proteins were present in sera from mice infected subcutaneously with MGAS 5005 or MGAS 315. Humans with documented GAS infections (pharyngitis, acute rheumatic fever, and severe invasive disease) also had serum antibodies reacting with many of the apparently secreted proteins, indicating that they were synthesized in the course of GAS-human interaction. The genes encoding four of the eight previously undescribed and apparently secreted culture supernatant proteins were cloned, and the proteins were overexpressed in Escherichia coli. Western blot analysis with these recombinant proteins and sera from GAS-infected mice and humans confirmed the immunogenicity of these proteins. Taken together, the data provide new information about the molecular aspects of GAS-host interactions.